Trophic State of The Tajwid Lake, Langgam District, Pelalawan Regency, Riau Province Based on Trophic State Index - Adithia Netanyahu Purba; Madju Siagian; Asmika H Simarmata2 (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Many activities in the Tajwid Lake contribute the input of organic and anorganic matter that affects the water quality, especially nutrient concentration in  waters. A research aims to understand the trophic state of the Tajwid Lake based on TSI has been conducted in March - April 2018. There were two sampling points, in the surface (0.5 m) and 2 secchi depth (1.1 m). Sampling were conducted 3 times, once/week. Water quality parameter measured were total phosphorus, chlorophyll - a, transparancy, temperature, dissolved oxygen, and pH. Results shown that the transparancy was 0.47 - 0.55 m, total phosphorus 0.323      - 0.624 mg/L, chlorophyll - a6.03-10.71 µg/L, temperature 29.5 - 30.3 0C, pH 5, and dissolved oxygen 4.96 - 5,66 mg/L. TSI(Trophic State Index) value of The Tajwid Lake was 70.01 - 72.19, and it indicates that the Tajwid Lake water is in hypereutrophic.Keywords: Water Quality, Carlson’ Trophic State Index, Hypereutrophic,Lake